Antenna Multiple Input Multiple Output Four Port Using Methods Stub and Defected Ground Structure for Ultra wide-band Applications - Denisa Putri Maharani; Yustini Yustini (Politeknik Negeri Padang, 2025)
Abstract— Multiple Input Multiple Output (MIMO) antennas using the Defected Ground Structure technique are able to produce wide bandwidth to meet Ultra Wide-Band (UWB) frequencies. UWB MIMO antennas have the advantages of reducing interference, improving isolation, and optimizing multipaths, thereby expanding coverage and improving signal quality. The challenge in designing MIMO-UWB antennas is to produce low mutual coupling with small antenna dimensions so that they can be used in portable devices. In this final project, the aim is to design a 4x4 UWB MIMO antenna using FR-4 substrate material with a dielectric constant (εr) of 4.3, a loss tangent of 0.035 and a material thickness of 1.6 mm. With dimensions of 45 x 45 x 1.6 ,mm-3. which has an Ultra-Wideband working frequency with a frequency range of 3.1 – 10.6 GHz. The results of the antenna simulation and measurement showed good performance with a simulated antenna operating frequency of 3.1–10.23 GHz, a minimum return loss of -49.85 dB, an isolation of ≤ -20 dB, and a maximum peak gain of 3.3 dBi at the frequency of 10.6 GHz with an omnidirectional radiation pattern. The measurement results show a working frequency of 3.2-10.64 GHz, a minimum return loss of -21.24 dB, and an Isolation of ≤ -20 dB. The designed four-port MIMO antenna parameters result in a simulated ECC and measurement < of 0.02 and a diversity gain of over 9.989, and a TARC of ≤ –10 dB. The measurement and simulation results show a good fit and are within the permissible limits, indicating good performance for UWB communication.